KAJIAN STILISTIKA DALAM TEKS AL-MUTAWASSIMĪN SEBAGAI BAHAN PEMBELAJARAN MATA KULIAH WAJIB STILISTIKA - Dhimas Muhammad Yasin (Center of Language and Cultural Studies, 2016)
This article discusses stylistic in Al-Mutawassimīn text, a Malay text manuscript. This study used qualitative descriptive design. The manuscript was evaluated its stylistics aspects and its characteristics were elaborated. The findings of analysis indicate that characteristics stylistic Al-Mutawassimīn text use a style of a hallmark of a genre of religious literature. The styles of genre were identified thorugh vocabulary, phrases, syntax, rhetoric or language means rhetorical and figurative language. Stylistics of Al-Mutawassimin are five kinds: (1) kinds of vocabulary are Indonesian, Arabic, Java, and some phrases in Arabic; (2) syntactics are in the form of the use of the conjunction